Towards detection of functional failure of equine articular cartilage : the metacarpophalangeal joint under scrutiny - Brommer, Harmen (Utrecht University, 2005)
Who is not fascinated by the elegance of the top-level dressage horse or impressed by the power and agility of the show jumper? The horse appeals to everybody’s imagination as an athlete pur sang, thanks to its powerful musculoskeletal system. However, there are several conditions that threat the proper functioning of the equine musculoskeletal system. Among these, osteoarthritis (OA) takes, as in man, the most prominent place. Driven by his eagerness to improve the diagnosis and prognostication of joint disease, Harold Brommer focuses in this thesis on the function and failure of articular cartilage, a tissue in which adequate functioning is equal to proper biomechanical behaviour. After setting the standard by determining the biomechanical characteristics of developing joints from birth to maturity, he develops the Cartilage Degeneration Index (CDI), an objective and quantitative measure of cartilage damage. The CDI is then used to trace how OA insidiously spreads over the joint surfaces of the equine metacarpophalangeal and metatarsophalangeal joints during the natural course of the disease. In the quest for an adequate and early diagnosis of OA, the index is also used to test the validity of the arthroscopic evaluation of a joint for cartilage damage and the value of a special indenter device that is meant to give information about material properties, i.e. biomechanical tissue characteristics. Results are promising, but further R&D is necessary before clinical use can be recommended. ‘Towards detection of functional failure of equine articular cartilage’ puts articular cartilage research in the perspective of function and performance. It gives an overview of present-day state of the art assessment of cartilage functionality in the horse, and, through its general concept, the conclusions are of equal relevance to man. In the end, it presents a clear vision where to go when aiming at further improvement of prevention, diagnosis, prognostication, and treatment strategies for degenerative joint disorders.
Keywords: Diergeneeskunde; horse; joint; cartilage; function; biomechanics; osteoarthritis; degeneration; quantification; diagnosis; prognostication